Low-voltage high-speed switched-capacitor circuits without voltage bootstrapper. - Lei Wang
Low-voltage high-speed switched-capacitor (SC) circuit design without using voltage bootstrapper is presented. The basic building block used for low-voltage SC circuit design is the auto-zeroed integrator (AZI), which can work at both low voltage and high sampling frequency. With this method, two low-voltage SC systems were successfully designed and implemented in 1.2-μm CMOS technology. The first one is a fully differential SC bandpass biquad working at 1.5 V and 5.0-MHz clock frequency. The measured Q value is 8.0 at the center frequency of 833 kHz. The second one is a fully differential fourth-order bandpass ΔΣ modulator that also works at 1.5 V and 5.0 MHz. Its measured third-order intermodulation is less than -78 dBc due to the low distortion characteristic of AZI. The measured signal-to-noise ratio of the modulator is 61 dB within the narrow band of 25 kHz centered at 1.25 MHz.
Keywords: 1.2 micron; 1.25 MHz; 1.5 V; 25 kHz; 5.0 MHz; 61 dB; 833 kHz; CMOS technology; LV switched-capacitor circuit design; Auto-zeroed integrator; Delta-sigma modulator; Fully differential SC bandpass biquad; High-speed SC circuit design; Low-voltage SC circuit design; Voltage bootstrapper; Fourth-order bandpass ΔΣ modulator; Fully differential ΔΣ modulator